46, XY complete gonadal dysgenesis with pubertal virilisation due to dysgerminoma/gonadoblastoma. Issue 7 (7th July 2020) - Alam, Sarah; Boro, Hiya; Goyal, Alpesh; Khadgawat, Rajesh
Abstract : Complete gonadal dysgenesis (CGD) or Swyer syndrome is characterised by sexual infantilism in a phenotypic female with 46, XY karyotype. Patients with gonadal dysgenesis and Y-chromosome material are at a high risk of developing gonadoblastoma and dysgerminoma. A 16-year-old girl presented with progressive virilisation, poor breast development and primary amenorrhea. On evaluation, she was found to have male-range serum testosterone, large abdominopelvic mass lesion, elevated germ cell tumour markers and 46, XY karyotype. She underwent surgical excision of left gonadal mass and right streak gonad, histopathology of which revealed dysgerminoma and gonadoblastoma, respectively. A diagnosis of virilising germ cell tumour arising in the setting of 46, XY CGD was, therefore, made. This case highlights a rare presentation of 46, XY CGD and the need to consider early prophylactic gonadectomy in patients affected with this rare condition. The presence of dysgerminoma/gonadoblastoma should be suspected if a hitherto phenotypic female with CGD undergoes virilisation.